2022
DOI: 10.1371/journal.pone.0261555
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms in non-alcoholic fatty liver disease are identified by perturbed lipid and lipoprotein metabolism

Abstract: Non-alcoholic fatty liver disease (NAFLD) and depression are common disorders and have bidirectional contributing relationships to metabolic syndrome. We aimed to determine whether a fasting serum signature of recent, self-reported depressive symptoms could be identified in a heterogeneous NAFLD cohort using nuclear magnetic resonance (NMR)-based metabolomics integrated with clinical chemistry. Serum nuclear magnetic resonance (NMR) metabolite profiles and corresponding clinical chemistry were compared between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…When these brain regions are DA-deficient, slow, uncoordinated movements and impaired cognition were reported, akin to the OFT and NORT results in WD-fed mice. These results further support that low brain DA concentrations are associated with motor depression and cognitive dysfunction in MASH [55][56][57][58].…”
Section: Discussionsupporting
confidence: 77%
“…When these brain regions are DA-deficient, slow, uncoordinated movements and impaired cognition were reported, akin to the OFT and NORT results in WD-fed mice. These results further support that low brain DA concentrations are associated with motor depression and cognitive dysfunction in MASH [55][56][57][58].…”
Section: Discussionsupporting
confidence: 77%
“…At an individual level, they can reduce the quality of life of those affected. Substantial epidemiological evidence exists for a bidirectional relationship between depression and obesity [147][148][149][150]. A meta-analysis of longitudinal studies found that obese individuals had a 55% increased risk of developing depression over time, while depressed persons were 58% more likely to become obese [147].…”
Section: Depression and Obesity: A Bidirectional Relationshipmentioning
confidence: 99%
“…Overall, there is increasing evidence of a bidirectional relationship between NAFLD and such mental health conditions, with reports suggesting that NAFLD may increase the risk of depression and anxiety, and that depressed individuals might be more likely to develop NAFLD, independently of other comorbidities [54]. However, it is noted that there may be other underlying factors in relation to these associations, including links between depression and/or anxiety and unhealthy lifestyle behaviours [10].…”
Section: Nafld and Mental Healthmentioning
confidence: 99%